S2k guidelines for skin and soft tissue infections Excerpts from the S2k guidelines for "calculated initial parenteral treatment of bacterial infections in adults – update 2018". (28th March 2019) - Sunderkötter, Cord; Becker, Karsten; Eckmann, Christian; Graninger, Wolfgang; Kujath, Peter; Schöfer, Helmut
Summary: These first German S2k guidelines for bacterial skin and soft tissue infections were developed as one chapter of the recommendations for "calculated initial parenteral treatment of bacterial infections" issued under the auspices of the Paul‐Ehrlich Society, of which the main part is presented here. Well‐calculated antibiotic therapies require precise diagnostic criteria. Erysipelas is defined as non‐purulent infection considered to be caused by beta‐hemolytic streptococci. It is diagnosed clinically by its bright‐red erythema and early fever or chills at disease onset. Penicillin is the treatment of choice. Limited soft tissue infection (cellulitis) is usually caused by Staphylococcus (S.) aureus, frequently originates from chronic wounds and presents with a more violaceous‐red hue and only rarely with initial fever or chills. Treatment consists of first‐ or second‐generation cephalosporins or flucloxacillin (IV). Severe cellulitis is a purulent, partially necrotic infection which extends through tissue boundaries to fascias and requires surgical management in addition to antibiotics. Moreover, it frequently fulfills the criteria for "complicated soft tissue infections", as previously defined by the Food and Drug Administration for use in clinical trials (they include comorbidities such as uncontrolled diabetes, peripheral artery disease, neutropenia). It requires antibiotics which besides S. aureus target anaerobic and/or gramnegative bacteria. The rare so‐called necrotizing skin and soft tissue infections represent a distinct entity. They are characterized by rapid, life‐threatening progression due to special bacterial toxins that cause ischemic necrosis and shock and need rapid and thorough debridement in addition to appropriate antibiotics. For cutaneous abscesses the first‐line treatment is adequate drainage. Additional antibiotic therapy is required only under certain circumstances (e.g., involvement of the face, hands, or anogenital region, or if drainage is somehow complicated). The present guidelines also contain consensus‐based recommendations for higher doses of antibiotics than those approved or usually given in clinical trials. The goal is to deliver rational antibiotic treatment that is both effective and well‐tolerated and that exerts no unnecessary selection pressure in terms of multidrug resistance.